A dynamic ubiquitous learning resource model with context and its effects on ubiquitous learning. Issue 1 (2nd January 2017) - Chen, Min; Yu, Sheng Quan; Chiang, Feng Kuang
ABSTRACT: Most ubiquitous learning researchers use resource recommendation and retrieving based on context to provide contextualized learning resources, but it is the kind of one-way context matching. Learners always obtain fixed digital learning resources, which present all learning contents in any context. This study proposed a dynamic ubiquitous learning resource model with context. The model has context information and a flexible content structure that allows contents to be adjusted dynamically in different contexts, thus providing learners the contextualized resources that best match their contexts. In order to verify the effects of the contextualized resources, a contrast experiment was carried out in a vocational school in China. The experimental results showed that the contextualized resources could better improve learners' learning achievement and efficiency, improve their self-learning efficiency while reducing their cognitive load. Learners thought the ubiquitous learning system which provided contextualized resources was more useful.